Analysis of factors that influence neurosurgical length of hospital stay among newly diagnosed pediatric brain tumor patients. Issue 1 (14th October 2019) - Hasan, Muhammad; Diep, Dion; Manoranjan, Branavan; Maharaj, Arjuna; Chaudhry, Sabrina; Shaheen, Saqib; Farrokhyar, Forough; Fleming, Adam J.; Ajani, Olufemi; Singh, Sheila K.; Yarascavitch, Blake
Abstract: Background: Postoperative length of stay (LOS) carries a high burden of healthcare costs. In resource‐intense specialties such as neurosurgery, it is imperative to identify factors that influence LOS to improve care. The current study investigates the potential for variables that affect clinical presentation, tumor characteristics, treatment modalities, and postoperative complications to impact overall LOS in pediatric brain tumor patients. Methods: A retrospective cohort study design was used with patients enrolled in the McMaster Pediatric Brain Tumor Study Group database. All patients up to 18 years of age, presenting with a newly diagnosed brain tumor admitted to and discharged from neurosurgery, were included. Patients were sorted into three cohorts: short LOS (≤3 days), extended LOS (≥20 days), and control LOS (4‐19 days). Results: Of the 124 patients included, 20 (65% male; median age: 9.1 years; range, 0.8‐17.4 years) were considered short LOS, 28 (61% male; median age: 4.7 years; range, 0.4‐14.7 years) were considered extended LOS, and 76 (57% male; median age: 8.5 years; range, 0.3–17.9 years) were considered control LOS. Variables that prolonged LOS were emesis at presentation ( P  < 0.001), developmental delay ( P  = 0.02), multiple surgeries ( P  = 0.004), tumor location ( P  < 0.05), subtotal resection ( P  = 0.02), feeding tube ( P  < 0.001), adjuvant chemoradiotherapy ( P  < 0.001), and posterior fossa syndrome ( P  = 0.004). Conclusions: This study identifies variables related to clinical presentation, tumor characteristics, treatment modalities, and postoperative complications associated with extended LOS. These findings uncover novel predictors of LOS that can be used to guide future research and improve health resource management.